MEKANISME UPAYA HUKUM VERZET TERHADAP PUTUSAN VERSTEK DALAM HUKUM ACARA PERDATA - Nugroho, Ferdiansyah; Anita Sinaga, Niru (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
This research discusses the mechanism of verzet legal action against verstek decisions in civil procedural law in Indonesia. Indonesia as a country of law ensures that every judicial decision provides justice and truth, and protects individual rights through the applicable legal system. One important aspect of civil procedural law is the existence of legal efforts that can be taken to correct decisions that are considered unfair. A verstek decision is a decision handed down without the defendant being present at the trial, even though he has been properly summoned. The defendant's absence without a valid reason provides a basis for the judge to hand down a verstek decision. However, for the sake of the principles of justice and a thorough examination of all parties, civil procedural law gives the defendant the right to file a verzet or opposition to the decision. This research aims to determine the purpose of implementing verzet legal remedies against verstek decisions in civil procedural law and to find out and analyze the mechanism for implementing verzet legal remedies against verstek decisions in civil procedural law. The research method used is normative juridical research with a statutory approach and case studies. This research analyzes the applicable legal provisions and related cases that have occurred in court. The research results show that verzet legal remedies are an important mechanism to ensure that each litigant gets a fair opportunity to defend themselves and present their arguments in court.